Robust expansion of HIV CAR T cells following antigen boosting in ART-suppressed nonhuman primates - Rust, Blake J. (Blood, 2020)
Chimeric antigen receptor (CAR) T cells targeting CD19(+) hematologic malignancies have rapidly emerged as a promising, novel therapy. In contrast, results from the few CAR T-cell studies for infectious diseases such as HIV-1 have been less convincing. These challenges are likely due to the low level of antigen present in antiretroviral therapy (ART)-suppressed patients in contrast to those with hematologic malignancies. Using our well-established nonhuman primate model of ART-suppressed HIV-1 infection, we tested strategies to overcome these limitations and challenges. We first optimized CAR T-cell production to maintain central memory subsets, consistent with current clinical paradigms. We hypothesized that additional exogenous antigen might be required in an ART-suppressed setting to aid expansion and persistence of CAR T cells. Thus, we studied 4 simian/HIV-infected, ART-suppressed rhesus macaques infused with virus-specific CD4CAR T cells, followed by supplemental infusion of cell-associated HIV-1 envelope (Env). Env boosting led to significant and unprecedented expansion of virus-specific CAR(+) T cells in vivo; after ART treatment interruption, viral rebound was significantly delayed compared with controls (P = .014). In 2 animals with declining CAR T cells, rhesusized anti–programmed cell death protein 1 (PD-1) antibody was administered to reverse PD-1–dependent immune exhaustion. Immune checkpoint blockade triggered expansion of exhausted CAR T cells and concordantly lowered viral loads to undetectable levels. These results show that supplemental cell-associated antigen enables robust expansion of CAR T cells in an antigen-sparse environment. To our knowledge, this is the first study to show expansion of virus-specific CAR T cells in infected, suppressed hosts, and delay/control of viral recrudescence.